2022
DOI: 10.1002/acr.24757
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Magnetic Resonance Imaging in Patients With Juvenile Idiopathic Arthritis in Clinical Remission

Abstract: Objective To define the prevalence of subclinical synovitis on magnetic resonance imaging (MRI) in a large cohort of patients with juvenile idiopathic arthritis (JIA) in clinical remission and to evaluate its predictive value in terms of disease flare and joint deterioration. Methods Ninety patients with clinically inactive JIA who underwent a contrast‐enhanced (CE)–MRI of a previously affected joint were retrospectively included. Each joint was evaluated for synovitis, tenosynovitis, and bone marrow edema. Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
0
8
0
1
Order By: Relevance
“…Particularly, it could be used prior to therapy to identify children who need more aggressive treatment and during the pharmacological treatment to monitor its efficacy and to assess more accurately their remission status. Moreover, it has been recently reported that persistent synovitis on hip MRI in children with JIA in clinical remission predicts disease flare [ 34 ]. Therefore, our scoring system could be extremely helpful in children in clinical remission where the depiction of a silent synovitis on MRI might allow prompt treatment with a possible considerable improvement of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, it could be used prior to therapy to identify children who need more aggressive treatment and during the pharmacological treatment to monitor its efficacy and to assess more accurately their remission status. Moreover, it has been recently reported that persistent synovitis on hip MRI in children with JIA in clinical remission predicts disease flare [ 34 ]. Therefore, our scoring system could be extremely helpful in children in clinical remission where the depiction of a silent synovitis on MRI might allow prompt treatment with a possible considerable improvement of disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, its application for treatment monitoring is still limited to clinical trials, as estimates of bone erosion and cartilage loss in children remain inherently imprecise. MRI is known to be constrained by several limitations, including cost, accessibility, and patient acceptance [ 12 , 13 ].…”
Section: Experts’ Opinion: Critical Pointsmentioning
confidence: 99%
“…A recent study by Mazzoni et al [ 12 ] found that subclinical synovitis and bone marrow edema detected on MRI in 65.5% and 46.7% of patients in their cohort, respectively, were the best predictors of disease relapse and joint deterioration, despite clinical remission. These findings have important implications for disease management [ 12 ].…”
Section: When Should Imaging Be Used In Juvenile Idiopathic Arthritis?mentioning
confidence: 99%
See 1 more Smart Citation
“…Studien konnten für den Nachweis einer subklinischen Aktivität und Hypervaskularisation von Gelenken und Sehnen bei Kindern mit JIA einen prädiktiven Wert für eine erneute Schubsituation nachweisen. Damit gewinnt die Gelenksonografie eine zunehmend wichtige Rolle im Treat-to-target-Konzept [10][11][12][13][14].…”
Section: Magnetresonanztomografieunclassified